X2 + 8x + 16 = 10x +16
x2 + 8x + 16
=
2x + 8x + 16
=
10x + 16
Chat with our AI personalities
x2 + 8x + 15 = (x + 3)(x + 5)
(x + 4)(x +4) or (x + 4)squared
x2 + 8x - 20 = (x - 2)(x + 10).
You ignore the constant part (-3 in this case), calculate half of the coefficient of the linear part (8, in this case), and square this half. (1/2 of 8 is 4; the square of 4 is 16). This gives you the perfect square x2 + 8x + 16. To get something equivalent to the original expression, you must both add and subtract 16, and include the term which I previously ignored (-3): x2 + 8x + 16 - 16 - 3, which you can write as (x2 + 8x + 16) - 16 - 3. The part within parentheses is the perfect square.
x² + 8x + 15 = (x + 5)(x + 3)